An annotated checklist of the Pericopina (Lepidoptera: Erebidae, Arctiinae, Arctiini) - Lamas, Gerardo (Zootaxa, 2017)
An annotated synonymic checklist of the subtribe Pericopina (Lepidoptera: Erebidae, Arctiinae, Arctiini) is presented, containing 332 species in 36 genera. One new replacement generic name, Myserla Lamas, is proposed for Sermyla Walker, 1854, a junior homonym of Sermyla H. Adams & A. Adams, 1854 (Mollusca). Thirteen new generic combinations are introduced, and twenty-four species-group taxa are downgraded to junior synonyms. Ten lectotypes are designated.